Labyrint? : Beeldententoonstelling. - Weyns, Guido; Van Bellingen, Stef; Zwijndrecht - Burcht (Burcht : [s.n.], 2000)
Claeyé, Catherine ; Clinckx, Christine ; De Backer, Luc ; Denijs, Christophe ; De Smet, Gery ; HAP ; Mulier, Wouter ; Paelinck, Lieven ; Prinsen, Bart ; van den Eerenbeemt, Rudolf ; Van Osselaer, Greg ; Velter, Yves ; Wortmann, Maria
Zwijndrecht - Burcht (Terrein aan de Schelde, Kerkstraat Burcht), 12 augustus - 15 oktober 2000
kunstcatalogus